THE EFFECT OF OWNERSHIP STRUCTURES AND FINANCIAL FIRM PERFORMANCE TOWARD EXECUTIVE COMPENSATION (EMPIRICAL STUDY ON CONSUMER CYCLICALS SECTOR COMPANIES LISTED IN INDONESIA STOCK EXCHANGE FOR THE PERIOD 2019) - Kamtono, Livia (Jurnal KIAFE, 2021)
This study aims to determine the effect of ownership structures and company"™s financial performance on executive compensation. The data is obtained from annual report of consumer cyclicals sector companies listed on the Indonesia Stock Exchange in 2019. The number of samples in this study is 85 out of 122 companies is taken through purposive sampling method in accordance with the criteria that has been created by the researcher. This research employs multiple linear regression analysis. The results of this study signify that ownership structures as measured by institutional ownership and managerial ownership have no effect on executive compensation. Company"™s financial performance measured by Net Profit Margin (NPM) has no effect on executive compensation, while as measured by Return on Equity (ROE) has a positive significant effect on executive compensation.